Usage of Color During Visualization of Rays Propagation Simulated with Monte-Carlo Method - Бирюков, Е.Д.; Рыжова, И.Г.; Волобой, А.Г. (Графикон - конференции по компьютерной графике и зрению, 2021)
This work describes specifics of rays colorization during visualization of trajectories of such rays obtained by Monte-Carlo simulation method in optical modeling systems. It is described how showing rays visualized with different colors in viewport of a CAD system can improve optical modeling process. Two basic methods of rays visualization are mentioned: directly during simulation process and after it. In more detail there is described application of coloring criteria for simulating different situations and problems with optical systems. In particular, drawing of an entire ray with some color specified by a criterion is mentioned, as well as drawing separate ray segments with different colors (when some criteria are applied separately to each segment). Construction of complicated criteria is described also (when some event occurred with ray or its segment should be repeated several times to satisfy the criterion). Besides that, drawing rays with natural colors is mentioned. Some words are also said about methods of commands and data synchronization for implementation of optical modeling system as a plug-in for existing CAD software, in particular, CATIA CAD.
Keywords: Raytracing; Monte-Carlo method; rays visualization; photorealistic images; optical modeling; lighting simulation